Molecular pathology of intraductal papillary mucinous neoplasms of the pancreas - Paini, Marina (Baishideng Publishing Group Inc, 2014)
Since the first description of intraductal papillary mucinous neoplasms (IPMNs) of the pancreas in the eighties, their identification has dramatically increased in the last decades, hand to hand with the improvements in diagnostic imaging and sampling techniques for the study of pancreatic diseases. However, the heterogeneity of IPMNs and their malignant potential make difficult the management of these lesions. The objective of this review is to identify the molecular characteristics of IPMNs in order to recognize potential markers for the discrimination of more aggressive IPMNs requiring surgical resection from benign IPMNs that could be observed. We briefly summarize recent research findings on the genetics and epigenetics of intraductal papillary mucinous neoplasms, identifying some genes, molecular mechanisms and cellular signaling pathways correlated to the pathogenesis of IPMNs and their progression to malignancy. The knowledge of molecular biology of IPMNs has impressively developed over the last few years. A great amount of genes functioning as oncogenes or tumor suppressor genes have been identified, in pancreatic juice or in blood or in the samples from the pancreatic resections, but further researches are required to use these informations for clinical intent, in order to better define the natural history of these diseases and to improve their management.